2022
DOI: 10.1007/s13313-021-00831-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Agrobacterium radiobacter, a new pathogen of pistachio

Abstract: Crown and stem gall caused by agrobacterial species is one of the most devastating diseases on different crops worldwide. In spring 2018, an alert concerning a disease forming galls on seedlings of pistachio in nurseries was received from Rafsanjan county, Kerman province, Iran. After isolation of bacteria from the galls by using conventional bacteriological methods, bacterial colonies were purified and selected for further analyses including biochemical, pathogenicity and molecular tests. Pathogenicity tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…L. Tokmakova et al (2019) found that Agrobacterium radiobacter improves plants nutrition with phosphorus, providing for the improvement of maize yields. However, caution should be taken when applying Agrobacterium radiobacter preparations because these bacteria are pathogens for some agricultural species, e.g., pistachio seedlings (Basavand et al, 2022), while some other crops should be provided with additional protection, especially potato (Borodaj & Parfeniuk, 2019).…”
Section: Note: N -The Dose Of Nitrogen Fertilisers Applied Kg Ha -1 ;...mentioning
confidence: 99%
“…L. Tokmakova et al (2019) found that Agrobacterium radiobacter improves plants nutrition with phosphorus, providing for the improvement of maize yields. However, caution should be taken when applying Agrobacterium radiobacter preparations because these bacteria are pathogens for some agricultural species, e.g., pistachio seedlings (Basavand et al, 2022), while some other crops should be provided with additional protection, especially potato (Borodaj & Parfeniuk, 2019).…”
Section: Note: N -The Dose Of Nitrogen Fertilisers Applied Kg Ha -1 ;...mentioning
confidence: 99%